Analysis and research on the thermal system of waste incineration power generation unit based on heat balance method - Xiao, Jian (Frontiers in Energy Research, 2023)
The thermal system of waste incineration power generation unit is simple and small in capacity, but the original parameters are few. It needs to calculate the thermal system and derive the parameters by using the conventional heat balance method to obtain the complete thermal system parameters. In this paper, an accurate and perfect thermodynamic model of waste incineration power generation is established to solve the problems of low thermal efficiency and high unit investment cost of the waste incineration power generation. To investigate the internal relationship between the incinerator unit structure, operating parameters, waste calorific value and waste combustion process, optimize the combustion status of different incinerators burning different waste, and realize its stable and efficient operation, it is necessary to study the impact of changing operating parameters and different incinerator structures on the waste incineration process, as well as the incineration law of a single incinerator unit structure burning waste with different calorific value. Based on the two-fluid model of primary oxygen supply and secondary oxygen supply, a newly developed thermodynamic model for waste incineration engineering was developed, and the direct coupling between the reciprocating grate and the incinerator was realized in the software. Using the conventional heat balance method and constant flow calculation, the flow parameters of the thermal system under the design condition are calculated through the design pressure parameters to calculate the power generation and thermal economy index of the condition; and the relevant steam extraction flow is checked and verified. The experimental results show that the net thermal efficiency of waste incineration increases from 19. 73% to 26. 40%, and the energy utilization efficiency also increases by 0. 18%. The net thermal efficiency of the optimized integrated power generation system is always higher than that of the independent power generation system more than 0.16%. The model method used in this paper can reduce the influence of incinerator arch structure on bed combustion to a greater extent, which makes the simulation results close to reality, greatly reduces the calculation cost, and is conducive to the industrial application of simulation in the field of waste incineration.